Runoff quantity estimation at University Malaysia Pahang (Gambang Campus) using storm water management model (SWMM) - Muhammad Zulhairi, Abdul Wahib (2019)
In this study, Storm Water Management Model (SWMM) is used to stimulate the runoff quantity at University Malaysia Pahang (UMP), Gambang Campus during the monsoon season. SWMM is model that used to run the stimulation of runoff quantity at the urban areas. SWMM can run a collection of sub catchments area that having a high intensity of rainfall that lead to the huge amount of surface runoff that can occur flash flood. The study area is in UMP Gambang as a catchment and have been divided into 9 sub catchments. The data are used in this study are three months rainfall data from October 2018 to December 2018 which are during the monsoon season in Pahang from two different station which are from RF3731018 (JKR Gambang) and UMP hobo using tipping bucket. The analysis of the result is depends on the parameter used in SWMM. The data from both station is calculated based on RMSE and best RMSE is 3.16 m3/s on November 2018 compared to 169.54 m3/s on October and 41.39 m3/s in December. So, the runoff data from November from the both station can be used for prediction of flash flood at UMP.